2021
DOI: 10.1371/journal.pone.0260322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic in the Portuguese population: Consumption of alcohol, stimulant drinks, illegal substances, and pharmaceuticals

Abstract: Background The measures implemented by governments worldwide to control and prevent the spread of the COVID-19 have impacted the populations and directly influenced individuals’ quality of life and consumption habits. Objective This work investigates the Portuguese population’s changes in alcohol, stimulants drinks, illegal substances, and pharmaceutical consumptions habits during the COVID-19 pandemic. Methods An online questionnaire comprising seven groups of questions–with one group referring to alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…As caffeine might be the most consumed psycho-stimulant around the world, and due to its likely complex effect on anxiety, further research in this field is needed. Moreover, results from recent studies suggested an increase in coffee, tea, and energy drink consumption during the COVID-19 pandemic [ 18 , 19 , 20 ]; as these beverages are the principal caffeine sources, caffeine intake might have also increased, and have become an additional risk factor for anxiety during this period and possibly beyond. The reported increased anxiety disorder prevalence during the COVID-19 pandemic in 2020–2021 underscores the urgency to strengthen mental illness prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As caffeine might be the most consumed psycho-stimulant around the world, and due to its likely complex effect on anxiety, further research in this field is needed. Moreover, results from recent studies suggested an increase in coffee, tea, and energy drink consumption during the COVID-19 pandemic [ 18 , 19 , 20 ]; as these beverages are the principal caffeine sources, caffeine intake might have also increased, and have become an additional risk factor for anxiety during this period and possibly beyond. The reported increased anxiety disorder prevalence during the COVID-19 pandemic in 2020–2021 underscores the urgency to strengthen mental illness prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The possible indirect impact of the COVID-19 pandemic on general health and lifestyle, for instance provoked by lockdowns, implementation of infection prevention measures and required self-isolation, has to be addressed. Increased alcohol consumption or intake of illegal substances–known to have a detrimental effect on health–have been shown during the second emergency state of the pandemic [ 22 ]. In contrast, the indirect impact of the pandemic could be effectively counteracted by stimulating the intake of a balanced diet, resulting in symbiosis by modulating the gut microbiota [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…When we compare this level with other countries, a US-cohort showed a rise in prescribed consumption of BZD (5.3%) and Z-hypnotics (1.4%) drugs at the start of the COVID-19 pandemic ( 15 ). In Europe, the results by Fernandez et al, using an online questionnaire to assess changes in illegal and legal psychoactive substances consumption habits among the Portuguese population during the COVID-19 pandemic, indicate that use of tranquilizers and anxiolytics increased by 10.8%, and use of sleep-inducing drugs by 7.8% ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was not observed in women with long-COVID-19. Different researches performed during the pandemic have demonstrated that psychotropic drug consumption rises with age, particularly after 65, in both men and women ( 15 , 16 , 23 ). One possible explanation for our results is that long-COVID-19 subjects in our study was a young population, with only 19% of the sample older than 55.…”
Section: Discussionmentioning
confidence: 99%